Recurrent invasive lobular carcinoma presenting as a ruptured breast implant - Botros, Maikel (Radiology and oncology (Ljubljana), 2012)
Background. For years, the treatment for invasive lobular carcinoma (ILC) has been mastectomy secondary to the lack of studies investigating the efficacy ofbreast conservation therapy on patients afflicted with ILC and due to the lack of long-term follow up investigating locoregional recurrence in this patient population. In this article we report the clinical course of a patientdiagnosed with ILC. Case report. We describe the case of a 50-year-old woman with stage IIB (T2N1M0) ER/PR positive right breast ILC who underwent a right modified radical mastectomy, postoperative chemotherapy, a prophylactic left simple mastectomy with bilateral breast reconstruction and tamoxifen. Approximately 12 years later, she presented with a deflated breast implant andrecurrent breast cancer with metastatic spread. She received palliative radiotherapy then palliative chemotherapy. Unfortunately, she succumbed to thecancer less than a year after being diagnosed with metastatic disease. Conclusions. This may be the first case report of a ruptured breast implant presenting at the same time as the diagnosis of recurrent breast cancer.
Keywords: Breast Implants; Breast Neoplasms; Carcinoma, Lobular; Dojka, novotvorbe; Dojka, vsadki; Karcinom lobularni; Mastectomy; Mastektomija; Middle Age; Neoplasm Recurrence, Local; Novotvorba, ponovitev lokalna; Srednja leta